Regional differences in housing price dynamics: Panel data evidence - Elias Oikarinen; Janne Engblom (Aboa Centre for Economics (ACE), 2014)
In this study, regional differences in housing price dynamics are examined empirically using panel data models. We concentrate on examining the momentum dynamics and the reversion speed towards fundamental price level. The analysis can be seen as a test for the validity of conventionally used fixed-effects panel models to analyse regional housing price dynamics. Based on data over 1988-2012, the findings indicate that the regional differences are generally quite small in the Finnish market. We find a notable difference between Helsinki, by far the greatest city in Finland, and the other cities regarding the strength of the momentum effect, though. The results also provide evidence of cointegration between regional housing prices and income. The long-term coefficient on income considerably varies across cities.
Keywords: R21; R31; C33; 330; housing price; dynamics; panel data; momentum; bubble